Structural Brain Abnormalities in Youth with Psychosis-Spectrum Symptoms - Satterthwaite, Theodore D. (JAMA Psychiatry, 2016)
IMPORTANCE: Structural brain abnormalities are prominent in psychotic disorders including schizophrenia. However, it is unclear when aberrations emerge in the disease process, and if such deficits are present in association with less severe psychosis-spectrum (PS) symptoms in youth. OBJECTIVE: To investigate the presence of structural brain abnormalities in youth with PS symptoms. DESIGN: The Philadelphia Neurodevelopmental Cohort (PNC) is a prospectively accrued community-based sample of nearly 10,000 youths who received a structured psychiatric evaluation. A subsample of 1,601 subjects underwent neuroimaging including structural magnetic resonance imaging. SETTING: The PNC is a collaboration between The Children’s Hospital of Philadelphia and the Hospital of the University of Pennsylvania. PARTICIPANTS: Youths ages 8–22 years identified through structured interview as having psychosis-spectrum features (PS, n=391), and typically developing comparison subjects without significant psychopathology (TD, n=400). MAIN OUTCOMES AND MEASURES: Measures of brain volume derived from T1-weighted structural neuroimaging at 3T. Analyses were conducted at global, regional, and voxelwise levels. Regional volumes were estimated with an advanced multi-atlas regional segmentation procedure; voxelwise volumetric analyses were conducted as well. Nonlinear developmental patterns were examined using penalized splines within a general additive model. PS symptom severity was summarized using factor analysis and evaluated dimensionally. RESULTS: Compared to the TD group, the PS group had diminished whole brain gray matter volume and expanded white matter volume. Voxelwise analyses revealed significantly lower gray matter volume in the medial temporal lobes as well as in frontal, temporal, and parietal cortex. Reduction of medial temporal lobe volume was correlated with PS symptom severity. CONCLUSIONS AND RELEVANCE: Structural brain abnormalities that have been commonly reported in adults with psychosis are present early in life in youth with PS symptoms, and are not due to medication effects. Future longitudinal studies could use the presence of such abnormalities in conjunction with clinical presentation, cognitive profile, and genomics to predict risk and aid in stratification to guide early interventions.